The origins of Christian democracy : politics and confession in modern Germany - Mitchell, Maria D., 1965- (University of Michigan Press, 2012)
This book is a pioneering contribution to the history of the founding of the West German political system after the Second World War. The political cooperation between Catholics and Protestants that resulted in the formation of the Christian Democratic Union (CDU) in occupied and early West Germany represented a significant change from a long history of hostility in confessional relations. Given that the CDU went on to dominate politics in West Germany well into the 1960s, Maria D. Mitchell argues that an understanding of what made this interconfessional party possible is crucial to an exploration of German history in the postwar period. She examines the political history of party formation as well as the religious beliefs and motivations that shaped the party's philosophy and positions. She provides an authoritative guide to the complex processes of maneuvering and negotiation that produced the CDU during 1945-46. The full range of political possibilities is discussed, including the suppressed alternatives to the Adenauer/Erhard axis that eventually defined the party's trajectory during the 1950s and the abortive Christian Socialism associated with Jacob Kaiser.